PENINGKATAN KOMPETENSI GURU DALAM MENYUSUN SILABUS KURIKULUM 2013 MELALUI BINTEK PADA GURU PENDIDIKAN AGAMA HINDU DI GUGUS I KECAMATAN KINTAMANI KABUPATEN BANGLI TAHUN 2018 - Miarta, I Wayan (GUNA WIDYA: JURNAL PENDIDIKAN HINDU, 2019)
The aims of this study is to improve teacher potential through Bimtek to compile the 2013 Curriculum Syllabus in Cluster 1 of Kintamani District, and Bangli Regency. This study was Regional School Action Research (PTSW) using two cycle designs and each cycle consists of four stages, namely: planning, action, observation, and reflection. In collecting the data, this study used measurement techniques, in the form of tests to obtain quantitative data. The observation sheet is used to obtain qualitative data. The data was analyzed by using descriptive analysis. There are 11 Hinduism Teachers, in Cluster 1 with less moderate and capable criteria. The teachers are ability to compile the syllabus as a classroom learning plan. The results showed that the quality of Hindu teachers in Cluster I gets enough title and the teacher who gets a good predicate is 45% so that the increase is 17% from enough to good. Furthermore, while the first cycle received a very good predicate as much as 18% in cycle 2 to 55% so that it experienced a 37% increase in the number of syllabus compilation from cycle I to cycle II. However, based on the result of this study was effective to achieve the target.